Recent Advances in Sensing Applications of Molecularly Imprinted Photonic Crystals - Fan, Jing; Qiu, Lili; Qiao, Yu; Xue, Min; Dong, Xiao; Meng, Zihui (Frontiers in Chemistry, 2021)
Photonic crystals (PhCs) with a brightly colored structure are novel materials and are widely used in chemical and biological sensing. Combining PhCs with molecular imprinting technology (MIT), the molecularly imprinted PhC (MIPC) sensors are fabricated, which can specifically recognize the target molecules. Aside from high sensitivity and selectivity, the MIPC sensors could recognize the naked eye detection because of its optical properties. In this review, an overview of recent advances in sensing applications of MIPC sensors including the responsive mechanisms, application in environmental monitoring, and the application to human health were illustrated. The MIPC sensors all responded to the analytes specifically and also showed high sensitivity in real samples, which provided a method to realize the rapid, convenient, naked eye, and real-time detection. Furthermore, the current limitations and potential future directions of MIPC sensors were also discussed.